Inhibition of STAT3 Signaling Pathway by Terphenyllin Suppresses Growth and Metastasis of Gastric Cancer - Yu, Dehua; Qi, Simin; Guan, Xiaoqing; Yu, Wenkai; Yu, Xuefei; Cai, Maohua; Li, Qinglin; Wang, Weiyi; Zhang, Weidong; Qin, Jiang-Jiang (Frontiers in Pharmacology, 2022)
Gastric cancer is a common type of malignant tumor with a relatively poor prognosis and presents a serious threat to global health. Signal Transducer and Activator of Transcription-3 (STAT3) has been strongly implicated in many cancers, and its constitutive activation promotes growth, angiogenesis, inflammation, and immune evasion. Therefore, considerable efforts have been put into developing effective and safe STAT3 inhibitors. In this study, we performed a virtual screening by molecular docking and found that terphenyllin, a marine-derived natural product, directly interacted with STAT3. We further found that terphenyllin inhibited the phosphorylation and activation of STAT3 and decreased the protein levels of STAT3-dependent target genes, including c-Myc and cyclin D1. Subsequently, we demonstrated that terphenyllin exerted its potent anticancer efficacy against gastric cancer in vitro and in vivo. Terphenyllin concentration-dependently inhibited growth, proliferation, and colony formation and induced cell cycle arrest and apoptosis of gastric cancer cells in vitro. Moreover, terphenyllin treatment suppressed the tumor growth and metastasis in a gastric cancer orthotopic mouse model without notable toxicity in vivo. Taken together, our results indicated that terphenyllin exerts its anticancer activity by inhibiting the STAT3 signaling pathway and may serve as a potent STAT3 inhibitor for gastric cancer treatment.